Anti-fibrotic effect of mycophenolate mofetil on Peyronie’s disease experimentally induced with TGF-β - Antoniassi, Thiago; Júnior, Fernando Nestor Fácio; Spessoto, Luís Cesar Fava; Guerra, Luiz Henrique [UNESP]; Campos, Silvana Spegorin [UNESP]; Taboga, Sebastião [UNESP] (Springer Nature, 2019)
The aim of the present study was to evaluate the histological, histochemical, and stereological changes caused by mycophenolate mofetil (MMF) on the tunica albuginea of rat penises submitted to an injection of transforming growth factor beta (TGF-β) for the induction of Peyronie’s disease (PD). Twenty adult male Wistar rats were divided into four groups: Control group; TGF-β group (TGF-β injection); MMF-7d group (treated with MMF 7 days after induction with TGF-β); and MMF-30d group (treated with MMF 30 days after induction with TGF-β). The steorological evaluation included the relative volume of different types of connective fibres of the tunica albuginea. The histochemical analysis revealed the fragmentation and degradation of elastin in the tunica albuginea. This process was partially reversed in the MMF-7d group and a situation very close to normality was observed in the MMF-30d group. In the collagen III/collagen I ratio it was observed increase in this ratio in the TGF-β (59.4 ± 5.53) and MMF-7d (49 ± 18.2) groups and a decrease in the MMF-30d group (28.7 ± 4), approaching normality. The injection of TGF-β promoted fibrotic alterations in the penile tunica albuginea in Wistar rats corresponding to PD. In this model, MMF acts as a regenerating anti-fibrotic agent.